Odpowiedzi

2010-04-11T20:29:43+02:00
A)3(2x+1)=4(x-2)
6x+3=4x-8
2x=-11/2
x=-5,5

b)2(2x-2)=3(3x+2)
4x-4=9x+6
-5x=10/-5
x=-2

c)(6x-1)1,2=2,3(x+1)
7,2x-1,2=2,3x+2,3
7,2x-2,3x=2,3+1,2
4,9x=3,5/4,9
x=0,7

d)
-x(1-6x)=2x(3x-1)
-x+6xkwadrat=6xkwadrat - 2x
x=0


2.
(z-1)*6,5=8
6,5z-6,5=8
6,5x=14,5/6,5
x=29/13 tu to kreska ulamkowa

5(2x-5)=3*4
10x-25=12
10x=37/10
x=3,7



10(9-3x)=8*1,5
90-30x=12
-30x=12-90/-30
x=2,6
1 5 1
2010-04-11T20:33:19+02:00
A) 3/x-2=4/2x+1

z proporcji:
6x + 3 = 4x - 8
6x - 4x = -8 - 3
2x = -11 | : 2
x = -5,5

b) 2/3=3x+2/2x-2

z proporcji:
4x - 4 = 9x + 6
4x - 9x = 6 + 4
-5x = 10 | : (-5)
x = -2

c) 6x-1/x+1=2,3/1,2

z proporcji:
(6x - 1)*1,2 = 2,3*(x+1)
7,2x - 1,2 = 2,3x + 2,3
4,9x = 3,5 | : 4,9
x ≈ 0,71

d) -x/3x-1=2x/1-6x

z proporcji:
-x + 6x² = 6x² -2x (6x² się skraca)
-x = -2x
x = 0

Zad. 2.
a)1/z-1=6,5/8
8 = 6,5z - 6,5
6,5 z = 14,5 | : 6,5
z ≈ 2,23

b)2x-5/3=4/5
12 = 10x - 25
10x = 37 | : 10
x = 3,7

c)10/1,5=8/9-3x
90 - 30x = 12
-30 x = -78 | : (-30)
x = 2,6
1 5 1